2009
DOI: 10.1016/j.schres.2009.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Why all the confusion? Experimental task explains discrepant semantic priming effects in schizophrenia under “automatic” conditions: Evidence from Event-Related Potentials

Abstract: The schizophrenia research literature contains many differing accounts of semantic memory function in schizophrenia as assessed through the semantic priming paradigm. Most recently, Event-Related Potentials (ERPs) have been used to demonstrate both increased and decreased semantic priming at a neural level in schizophrenia patients, relative to healthy controls. The present study used ERPs to investigate the role of behavioral task in determining neural semantic priming effects in schizophrenia. The same schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 42 publications
2
56
1
Order By: Relevance
“…In contrast, a few other schizophrenia studies have found smaller than normal N400 amplitudes to contextually related targets and increased N400 relatedness priming effects (Kreher et al 2009;Kreher et al 2008;Mathalon et al 2002;Salisbury 2008). However, these latter data appear to be specific to short primetarget stimulus-onset asynchronies (SOAs; i.e., the time interval between the onsets of the two stimuli) of <300 ms, weakly related targets, and patients with disorganized speech and are thus suggestive of rapid automatic priming of weakly associated concepts in this subset of patients (Ditman and Kuperberg 2007;Kreher et al 2009;Salisbury 2008). On balance, however, N400 studies of schizophrenia patients provide evidence of a general reduction in semantic priming, at least at SOAs of approximately 300 ms or greater, during which more controlled or strategic cognitive processing is normally thought to occur.…”
Section: Introductioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In contrast, a few other schizophrenia studies have found smaller than normal N400 amplitudes to contextually related targets and increased N400 relatedness priming effects (Kreher et al 2009;Kreher et al 2008;Mathalon et al 2002;Salisbury 2008). However, these latter data appear to be specific to short primetarget stimulus-onset asynchronies (SOAs; i.e., the time interval between the onsets of the two stimuli) of <300 ms, weakly related targets, and patients with disorganized speech and are thus suggestive of rapid automatic priming of weakly associated concepts in this subset of patients (Ditman and Kuperberg 2007;Kreher et al 2009;Salisbury 2008). On balance, however, N400 studies of schizophrenia patients provide evidence of a general reduction in semantic priming, at least at SOAs of approximately 300 ms or greater, during which more controlled or strategic cognitive processing is normally thought to occur.…”
Section: Introductioncontrasting
confidence: 60%
“…Numerous studies have found evidence for larger (more negative) than normal N400 amplitudes in response to contextually related items, and smaller than normal N400 semantic priming effects, in schizophrenia (Condray et al 2003;Condray et al 2010;Ditman and Kuperberg 2007;Kiang et al 2011;Kiang et al 2008;Kostova et al 2005;Kostova et al 2003;Laurent et al 2010;Mathalon et al 2010;Ohta et al 1999;Salisbury 2010;Salisbury 2008;Strandburg et al 1997). In contrast, a few other schizophrenia studies have found smaller than normal N400 amplitudes to contextually related targets and increased N400 relatedness priming effects (Kreher et al 2009;Kreher et al 2008;Mathalon et al 2002;Salisbury 2008). However, these latter data appear to be specific to short primetarget stimulus-onset asynchronies (SOAs; i.e., the time interval between the onsets of the two stimuli) of <300 ms, weakly related targets, and patients with disorganized speech and are thus suggestive of rapid automatic priming of weakly associated concepts in this subset of patients (Ditman and Kuperberg 2007;Kreher et al 2009;Salisbury 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some other studies of schizophrenia patients have found smaller than normal N400 amplitudes to target stimuli related to preceding prime stimuli, and increased N400 semantic priming effects (Mathalon et al, 2002;Kreher et al, 2008;Salisbury, 2008;Kreher et al, 2009). Importantly, this pattern appears specific to short prime-target stimulus-onset asynchronies (SOAs) of less than approximately 300 ms, and patients with disorganized speech; and is thus thought to reflect an excess of rapid spread of activation in the semantic network of disorganized patients in particular (Ditman and Kuperberg, 2007;Salisbury, 2008;Kreher et al, 2009).…”
Section: Introductionmentioning
confidence: 87%
“…Importantly, this pattern appears specific to short prime-target stimulus-onset asynchronies (SOAs) of less than approximately 300 ms, and patients with disorganized speech; and is thus thought to reflect an excess of rapid spread of activation in the semantic network of disorganized patients in particular (Ditman and Kuperberg, 2007;Salisbury, 2008;Kreher et al, 2009). Thus, this "hyperpriming" is not necessarily mutually exclusive with the presence of semantic priming deficits over longer time intervals in schizophrenia patients more generally.…”
Section: Introductionmentioning
confidence: 99%
“…Increased N400 semantic priming effects have been reported in patients with psychotic disorder, with abnormally small N400 amplitudes to directly associated words (compared to the unrelated condition) in patients with non-FTD (Mathalon et al, 2002(Mathalon et al, , 2010, and indirectly related words in patients with FTD (Kreher et al, 2010(Kreher et al, , 2008) at short SOA, indicative of a broader spreading of activation in the semantic network. In contrast, abnormally reduced N400 semantic priming effects have also been found in patients with psychotic disorder, with larger N400 amplitudes for the direct and indirect associative conditions (indicating no difference between the associatively/indirectly related and the unrelated N400 amplitude) at short and long SOA (Condray et al, 2003;Kiang et al, 2008).…”
mentioning
confidence: 97%